Proteção Diferencial de Transformadores Usando a Transformada Wavelet - Silva, Paulo Henrique Gonçalves Leonel da [UNESP] (2014)
In this work it is presented a numerical algorithm for transformer differential protection. The principal objective of this algorithm is the search of an efficient distinction between fault currents and magnetization currents, also known by inrush currents that can induce false tripping of differential relays. The wavelet transform is used to discern fault currents from inrush currents, using the energy conservation principle that is available in this kind of transform. The numerical algorithm was developed in the software MATLAB and the electric circuit, used as a test, is simulated in software ATP/EMTP due to its already consolidated use and reliability of results when real technical data from power electric systems are available. The presented simulations and results indicates that the developed technique is shown efficient according to typical protection relay behaviours